2007
DOI: 10.1038/sj.cdd.4402213
|View full text |Cite
|
Sign up to set email alerts
|

Enforced covalent trimerization increases the activity of the TNF ligand family members TRAIL and CD95L

Abstract: Variants of human TRAIL (hTRAIL) and human CD95L (hCD95L), encompassing the TNF homology domain (THD), interact with the corresponding receptors and stimulate CD95 and TRAILR2 signaling after cross-linking. The murine counterparts (mTRAIL, mCD95L) showed no or only low receptor binding and were inactive/poorly active after cross-linking. The stalk region preceding the THD of mCD95L conferred secondary aggregation and restored CD95 activation in the absence of cross-linking. A corresponding variant of mTRAIL,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
101
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(105 citation statements)
references
References 23 publications
4
101
0
Order By: Relevance
“…Recently, we further demonstrated that conversion of the monovalent scFv-scTRAIL fusion protein into a bivalent diabodyscTRAIL fusion protein-exhibiting two antigen-binding sites and two scTRAIL moieties-further increased cytotoxic activity against tumor cells without increasing cytotoxicity toward normal cells (11). This is most likely due to the fact that the dimeric scTRAIL fusion proteins are capable of mimicking the activity of membrane-displayed, that is, multivalent, TRAIL, leading to increased receptor signal complex formation and activation (12,13). The dimerization of scTRAIL in the diabody-scTRAIL fusion protein is mediated by the antibody moiety, thus combining targeting and dimerization in the same module.…”
Section: Introductionmentioning
confidence: 78%
“…Recently, we further demonstrated that conversion of the monovalent scFv-scTRAIL fusion protein into a bivalent diabodyscTRAIL fusion protein-exhibiting two antigen-binding sites and two scTRAIL moieties-further increased cytotoxic activity against tumor cells without increasing cytotoxicity toward normal cells (11). This is most likely due to the fact that the dimeric scTRAIL fusion proteins are capable of mimicking the activity of membrane-displayed, that is, multivalent, TRAIL, leading to increased receptor signal complex formation and activation (12,13). The dimerization of scTRAIL in the diabody-scTRAIL fusion protein is mediated by the antibody moiety, thus combining targeting and dimerization in the same module.…”
Section: Introductionmentioning
confidence: 78%
“…Using the flanking EcoRI (5Ј) and XbaI (3Ј) sites, the TWEAK domain-containing DNA fragment of FLAG-TWEAK-pCR3 was subcloned in pCR3 derivatives with an N-terminal GpL-FLAG epitope-TNC or a LeaderhIgG1(Fc)-FLAG epitope encoding cassette to allow expression of secretable GpL-FLAG-TNC-TWEAK and Fc-FLAG-TWEAK. TNC refers to the trimerization domain of chicken tenascin C, which serves to stabilize the trimeric assembly of ligands of the TNF family and thus reduces formation of inactive misfolded protein species (26,27). The G. princeps luciferase (GpL)-encoding DNA fragment used was a synthetic product of the complete reading frame of the GpL gene with human codon usage.…”
Section: Methodsmentioning
confidence: 99%
“…1, A-C). We further included a small trimerization domain from tenascin C (ϳ3 kDa) to stabilize the trimeric assembly of TWEAK and to minimize the formation of inactive misfolded ligand species (26,27). After 4 -6 days of cultivation, cell culture supernatants of Hek293 cells stably transfected with expression plasmids encoding secretable GpL-FLAG-TNC-TWEAK and FLAG-TWEAK contained typically 40 -80 g of the recombinant protein per 15-cm cell culture Petri dish.…”
mentioning
confidence: 99%
“…36), Metridia longa luciferase (MlL), secreted alkaline phosphatase (SEAP), yellow fluorescent protein (YFP), and an O 6 -alkylguanine-DNA-alkyltransferase-based SNAP tag as reporter domains. We recently observed that the integrity of the trimeric nature of some soluble TNF ligands benefits from the N-terminal fusion of the small (ϳ3 kDa) trimerization domain of tenascin-C (37,38). We, therefore, included this domain also in our fusion proteins between the reporter domain (including a FLAG tag) and the THD.…”
Section: Membrane Cd95l Is Superior To Soluble Cd95l In Triggering CDmentioning
confidence: 99%